A modeling approach to evaluate long-term outcome of prophylactic and on demand treatment strategies for severe hemophilia A - Kathelijn Fischer; Maurice E. Pouw; Daniel Lewandowski; Mart P. Janssen; H. Marijke van den Berg; Ben A. van Hout (Haematologica, 2011)
Background Severe hemophilia requires life-long treatment with expensive clotting factor concentrates; studies comparing effects of different therapeutic strategies over decades are very difficult to perform. A simulation model was developed to evaluate the long-term outcome of on demand, prophylactic and mixed treatment strategies for patients with severe hemophilia A.Design and Methods A computer model was developed based on individual patients’ data from a Dutch cohort study in which intermediate dose prophylaxis was used and a French cohort study in which on demand treatment was used, and multivariate regression analyses. This model simulated individual patients’ life expectancy, onset of bleeding, life-time joint bleeds, radiological outcome and concentrate use according to the different treatment strategies.Results According to the model, life-time on demand treatment would result in an average of 1,494 joint bleeds during the hemophiliac’s life, and consumption of 4.9 million IU of factor VIII concentrate. In contrast, life-time intermediate dose prophylaxis resulted in a mean of 357 joint bleeds and factor consumption of 8.3 million IU. A multiple switch strategy (between prophylactic and on demand treatment based on bleeding pattern) resulted in a mean number of 395 joint bleeds and factor consumption of 6.6 million IU. The estimated proportion of patients with Pettersson scores over 28 points was 32% for both the prophylactic and the multiple switching strategies, compared to 76% for continuous on demand treatment.Conclusions The present model allows evaluation of the impact of various treatment strategies on patients’ joint bleeds and clotting factor consumption. It may be expanded with additional data to allow more precise estimates and include economic evaluations of treatment strategies.